Off-Pump Revascularization in Moderate Ischemic Mitral Regurgitation - Ates, Mehmet Sanser; Alptekin, Gulen Sezer; Demirozu, Zumrut Tuba; Zorman, Yilmaz; Akcevin, Atif (The Thoracic and Cardiovascular Surgeon, 2024)
Ischemic mitral regurgitation (IMR) is associated with high mortality and poor outcomes. The surgical management of moderate IMR is still an object of debate.Patients with moderate IMR who underwent isolated off-pump coronary bypass grafting (OPCAB) with facile stabilization between January 2015 and February 2022 were analyzed. The primary endpoint was the remaining IMR and echocardiographic findings while the secondary outcomes were defined as mortality, major adverse events, and postoperative functional status.Of 541 patients who underwent isolated OPCAB in this period, there were 62 patients with concomitant moderate IMR. The mean follow-up period was 19.4 ± 21.6 months. The median number of the coronary anastomosis was 4. In 58.06% (n = 36), the regurgitation regressed. Left atrial (LA) diameter significantly decreased postoperatively (p = 0.040). Increased LA diameter was associated with increased major adverse events (p = 0.010). Rehospitalization rates were higher in low ejection fraction (EF). The postoperative poor functional status (New York Heart Association [NYHA] III–IV) was correlated with an increased postoperative left ventricular end-systolic diameter (LVESD; 41.75 ± 6.13 vs. 34.79 ± 6.8 mm, p = 0.05). Mortality (4.8%, n = 3) was associated with older age and increased preoperative systolic pulmonary artery pressure (PAP; p = 0.050 and p = 0.046, respectively).LA diameter, LVESD, mean systolic PAP, left ventricular ejection fraction (LVEF), and age are important predictors for outcomes in IMR. Remaining IMR per se is not directly correlated with increased mortality and major adverse cardiac and cerebrovascular events. The facile stabilization technique we used appears to be advantageous due to the feasibility of full revascularization of all intended vessels, particularly of the inferoposterior wall by providing excellent vision without compression of the heart.
Keywords: off-pump surgery; CABG; echocardiography (all modalities; applications)